Tradisi Pemikiran Moderasi Beragama Nahdlatul Ulama - Moh Ashif Fuadi (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
AbstractThis research illustrates the values of religious moderation that contrast with the body of Nahdlatul Ulama (NU). Since the establishment of NU Hadratussyaikh K.H. Hashim Asy'ari has initiated the concept of a moderate Islamic pattern in Indonesia which was then continued by the next generation of NU including K.H. Abdurrahman Wahid (Gus Dur). Through descriptive qualitative research methods with a historical analytical approach, this study produced conclusions about the foundation of religious moderation initiated by Hashim Ash'ari by following the aqidah of Ash'ariah, madzhab fiqih shafi'i, and Sufism. The value of religious moderation is also reflected in the concepts of tasamuh, tawasuth, and tawazun. In addition, the tradition of NU moderation is reflected in the trilogy of Islamic, insaniyah, wathaniyah ukhwah. NU moderate thinking is very instrumental in internalizing wasathiyah through the acceptance of madzhab, Aqidah Asy'ariyah, the integration of Islam with nationality, and through the cultural movement spearheaded by Gus Dur interfaith dialogue movement.